Pemberdayaan Kader Posyandu dalam Penerapan Hydrotherapy untuk Stimulasi Tumbuh Kembang Bayi - Devi Elfita Sari; Hanik Khairun Nisa (Universitas Nusantara PGRI Kediri, 2025)
Hydrotherapy is a stimulation approach that uses water as a therapeutic medium to facilitate infant motor development, hydrostatic pressure, and warm temperature.This community service activity aimed to strengthen the capacity of Posyandu cadres in Gandus Village, Palembang City, by training them to apply hydrotherapy as a practical technique for stimulating infant growth and motor development at the community level. The program employed educational sessions and hands-on demonstrations, covering basic theoretical concepts of hydrotherapy, its developmental benefits for infants aged 6–12 months, and essential safety principles.The findings indicated a marked improvement in the cadres’ knowledge and practical skills, as reflected in increased post-test scores and their ability to independently demonstrate each step of the hydrotherapy procedure according to established guidelines. Participants expressed enthusiasm toward integrating hydrotherapy into routine Posyandu activities, noting that the method was simple, feasible, and well-suited for community settings. Overall, this program successfully enhanced the competence of Posyandu cadres in providing safe and effective motor development stimulation through hydrotherapy. The activity also holds potential to support early detection of developmental delays and to strengthen community-based health promotion efforts focused on improving infant growth and developmental outcomes.